Spline adjustment for modelling solar intermittences - Raúl Alberto López-Meraz; Luis Hernández-Callejo; Luis Omar Jamed-Boza; Víctor Alonso-Gómez (Revista Facultad de Ingeniería Universidad de Antioquia, 2020)
One of the reasons why photovoltaic technology is not massively installed is its variation in production. This variation is due to intermittences in the solar resource. Based on real data from the microgrid of the Renewable Energy Development Center (CEDER, Spain) and another scenario in Xalapa (México), the study determines the solar intermittences produced and grouped monthly. The period of data acquisition, in the first study, was from May 30th, 2012 to March 3rd, 2015 with the help of a Baseline Surface Radiation Network (BSNR) team; in the second, 2014 measurements were obtained from a meteorological station certified by the National Meteorological System (SMN). The analysis is based on the determination of monthly frames of reference for radiation by third-degree spline adjustments with smoothing, using the JUMP statistical application software (JMP © 2009, SAS Institute, version 8.0.2). The results of the analyses have provided important information to understand the unstable appearance of solar radiation and, in turn, will be the basis of a control system to optimize photovoltaic production.